2010
DOI: 10.1007/s10142-010-0172-5
|View full text |Cite
|
Sign up to set email alerts
|

The gene structure and promoter region of the vaccine target aminopeptidase H11 from the blood-sucking nematode parasite of ruminants, Haemonchus contortus

Abstract: Aminopeptidase H11, an integral membrane glycoprotein present only in the gut of Haemonchus contortus, could provide substantial protection as shown by 90% reduction in fecal egg counts, while its recombinant version expressed in E. coli induced little. To investigate the characteristics further, we amplified mRNA of H11 gene via reverse transcriptase polymerase chain reaction, followed by isolation of its 1,517-bp 5'-flanking region and determination of its genomic organization. The H11 gene contained 25 exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…Analysis of overlapping H. contortus scaffolds, in addition to performing PCR on H. contortus genomic DNA, showed that all 5 isoforms are tandemly arranged in the genome (Figure 1A). Our findings expand on previous data [41], which showed linkage of H11-4 and H11 genes, and suggest that the H11 gene family has arisen through recent duplication and divergence. The encoded proteins share 62-75% amino acid identity, with the zinc binding domain (HELAH) and exopeptidase motif (GAMEN) characteristic of N-aminopeptidases highly conserved in all isoforms (Additional file 2).…”
Section: Resultssupporting
confidence: 90%
“…Analysis of overlapping H. contortus scaffolds, in addition to performing PCR on H. contortus genomic DNA, showed that all 5 isoforms are tandemly arranged in the genome (Figure 1A). Our findings expand on previous data [41], which showed linkage of H11-4 and H11 genes, and suggest that the H11 gene family has arisen through recent duplication and divergence. The encoded proteins share 62-75% amino acid identity, with the zinc binding domain (HELAH) and exopeptidase motif (GAMEN) characteristic of N-aminopeptidases highly conserved in all isoforms (Additional file 2).…”
Section: Resultssupporting
confidence: 90%
“…From the complete, assembled transcriptome representing all eight stages or sexes of H. contortus (see Schwarz et al, 2013), we identified and isolated 1,066 assembled transcripts based on their homology matches (E-value cut off: 10 -5 ) to all five known h11 genes (designated h11-1 to h11-5; GenBank accession numbers AJ249941, AJ249942, AJ311316, FJ481146 and X94187, respectively; Graham et al, 1993;Smith et al, 1997;Zhou et al, 2010). Then, we identified genomic scaffolds containing regions of homology to known H11 genes Roberts et al, 2013) by mapping (E-value cut-off: 10 -5 ) these assembled transcripts (n = 1,066) using BLAT (Kent, 2002).…”
Section: Identification Of Genomic Scaffolds Containing Genes Encodinmentioning
confidence: 99%
“…Subsequently, two other isoforms (H11-4 and -5) were sequenced and deposited in the GenBank database (accession nos. FJ481146 and X94187; Smith et al, 1997;Zhou et al, 2010). Although vaccination success was achieved using purified, native H11, and cDNA clones were patented Graham et al, 1993), to date, vaccination of sheep with recombinant forms of H11 has not achieved the level of protection required for a practical or commercial vaccine (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Haemonchus contortus is a highly pathogenic bloodingsucking parasitic nematode, causing ruminants to lose weight, suffer anemia and even death in serious infection (Zhou et al, 2010). Haemonchosis occurs mostly in spring and autumn (Tembely et al, 1997;Todd et al, 1976).…”
Section: Introductionmentioning
confidence: 99%